Nilai-Nilai Kepribadian Oei Tjoe Tat Sebagai Nasionalis Etnis Tionghoa di Indonesia - Ari Hermawan; Budi Purnomo; Nelly Indrayani (Jurnal Siginjai, 2021)
This research is entitled "Oei Tjoe Tat's Personality Values ​​as a Chinese Ethnic Nationalist in Indonesia". The author focuses on a theme of personality analysis of the character Oei Tjoe Tat who holds idealism based on the ideals so that Indonesia becomes a place to unite all levels of society by not giving treatment that distingu is hes between ethnicity, nation, religion and race and up holds justice and fosters a sense of kinship in every community. An individual self. This study aims to describe and get a detailed and detailed picture regarding the position of the Chinese ethnicity in Indonesia which has become an inseparable part of the Indonesian nation itself. In this article, the author uses the historical research method with a literature study approach. As for what can be drawn from a conclusion in this study that during colonialism many ethnic Chinese communities participated in the world of the national movement. They have a considerable role in the independence of Indonesia. Likewise, after independence, many ethnic Chinese communities participated in the wheels of government, including Oei Tjoe Tat who became one of the big names among the political elite during the Soekarno government and what he had contributed should also be used as an example and role model in fighting for national ideals